Manajemen Kurikulum Bahasa Arab di Pesantren Manba’ul ‘Ulum - Fina Nur Fadhilah fina; Nasiruddin (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2023)
The curriculum is a set of plans and procedures that serve as guidelines for achieving learning programs in educational institutions. The Arabic language learning curriculum consists of a number of materials or lesson content, learning experiences, and educational planning programs that students must achieve in order to achieve certain educational goals. To achieve the goals of learning Arabic in an educational institution, of course, a good and appropriate learning management is needed. This study aims to find out how the management of learning Arabic consisting of planning, implementation, and evaluation at the Manba'ul 'ulum Islamic boarding school. This study uses a qualitative research method with a qualitative descriptive model. The results of this study are that the Manba'ul 'ulum Islamic boarding school has 2 curricula, namely the non-formal curriculum or pesantren. In the management of learning Arabic at the Manba'ul 'ulum Islamic boarding school, it has met good educational standards, namely by planning, implementing, and evaluating systematically so that the expected learning objectives can be achieved.